Studi Kualitas Hadis Pada Kitab Irsyadul ‘Ibad Karya Syekh Zainuddin Al –Malibari - Rivai Harahap; Rahima Sikumbang (Journal of Innovative and Creativity, 2026)
Irsyadul ‘Ibad is a hadith book authored by Shaykh Zainuddin al-Malibari, a prominent scholar from Malabar, India. This book has been widely adopted by Muslims. The hadiths contained in it are sometimes presented incompletely, often quoting only the matn without including the isnad. One such example is the hadith on wasiya (bequest) found in Irsyadul ‘Ibad by Shaykh al-Malibari. The author of this study chose the theme of wasiya because it is highly important to examine, as it concerns inheritance, the rights of heirs, and the responsibilities of a Muslim after death.Through scholarly investigation, the quality of these hadiths can be identified, while also evaluating the accuracy of the quotations. This process makes it possible to uncover potential errors or weaknesses in their chains of transmission. The research applies a library research method with a descriptive-analytical approach. The steps undertaken in data collection and processing include: conducting takhrij al-hadith by utilizing companion indexes, the initial segment of the matn, and keyword indexes; arranging a complete scheme of the chain of transmission for each hadith; and performing a comprehensive sanad criticism.The conclusion is drawn based on these three stages. The findings reveal that the hadiths on wasiya contained in Irsyadul ‘Ibad by al-Malibari can be classified as follows: the first, second, third, and fourth hadiths are categorized as da‘if (weak), while the overall matn is classified as maqbul (acceptable).